Maternal methadone therapy increases QTc interval in newborn infants. Issue 2 (16th November 2010) - Parikh, R; Hussain, T; Holder, G; Bhoyar, A; Ewer, AK
Abstract : Introduction: Prolongation of the QT interval is a risk factor for sudden death. Methadone treatment is a well-recognised cause of QT interval lengthening in adults. The effect of maternal methadone treatment on the QT interval of the newborn infant is not known. This is the first prospective study of corrected QT (QTc) interval in infants born to mothers receiving methadone. Aim: To compare QTc interval in infants born to mothers receiving methadone therapy with healthy controls. Method: Twenty-six term infants (median gestation 38 weeks, range 37–40) born to mothers on methadone therapy had ECG recordings on days 1, 2, 4 and 7. The QTc interval was calculated using the Bazzett formula. Results for days 1 and 2 were compared with healthy matched control infants born to mothers who were not receiving methadone. Results for days 4 and 7 were compared with published normal values. Results: In the methadone group, the QTc interval was significantly prolonged on days 1 and 2 of life. On days 4 and 7, this increase was no longer present. None of the infants in either group had any evidence of significant cardiac rhythm disturbance. Conclusion: Maternal methadone therapy can cause transient prolongation of the QTc interval in newborn infants in the first 2 days of life. Newborns exposed to methadone are at risk of cardiac rhythm disturbances. Bradycardia, tachycardia or an irregular heart rate in an infant born to a mother on methadone treatment should prompt investigation with a 12-lead ECG.